Konstitusionalisme Digital di Indonesia : Mengartikulasikan Hak dan Kekuasaan dalam Masyarakat Digital - Subekti, Nanang; Handayani , I Gusti Ayu Ketut Rahmi; Hidayat, Arief (Pustaka Peradaban, 2023)
The digital revolution has significant implications for the constitutional dimension. Digital platforms play a critical role in the intersections and clashes of power between market logic, public authorities, and citizens' rights. Constitutional principles are needed to guarantee the protection and implementation of the basic rights of citizens as well as limiting powers. The protection of personal data is a key component of the digital Constitutionalism framework to ensure that basic rights and democratic values are protected in the digital age. Efforts to protect these basic rights in Indonesia are manifested in various personal data protection regulations that are continuously being refined, even though Indonesia is lagging in its development. Revolusi digital memunculkan implikasi yang signifikan terhadap dimensi konstitusional. Platform digital semakin memainkan peran penting di persimpangan dan benturan kekuasaan antara logika pasar, otoritas publik dan hak warga negara. Prinsip-prinsip konstitusional diperlukan untuk menjamin perlindungan dan pelaksanaan hak-hak dasar warga negara sekaligus juga pembatasan terhadap kekuasaan yang tidak bertanggungjawab. Perlindungan data pribadi adalah komponen kunci dari kerangka kerja Konstitusionalisme digital untuk memastikan terlindunginya hak-hak dasar dan nilai-nilai demokrasi di era digital. Upaya perlindungan hak dasar itu di Indonesia diwujudkan dalam berbagai regulasi perlindungan data pribadi yang terus disempurnakan, walaupun Indonesia termasuk yang tertinggal dalam perkembanganya.